Investigation of the Antiproliferative Action of the Quinoline Alkaloids Kokusaginine and Skimmianine on Human Cell Lines - Molnar, Judit; Ocsovszki, Imre; Puskas, Laszlo; Ghane, Tannaz; Hohmann, Judit; Zupko, István (Current Signal Transduction Therapy, 2013)
Natural products play a crucial role in research into innovative antiproliferative agents. More than 60% of anticancer drugs involve compounds of natural origin. The aim of the present study was to determine the cytotoxicity effects of 11 quinoline alkaloids isolated from plants of the Rutaceae family. The MTT assay was used to identify the antiproliferative effects of the tested compounds on human adherent cancer cell lines (HeLa, A431, MCF7 and A2780). Two of these alkaloids, kokusaginine and skimmianine, were found to inhibit the proliferation of cancer cells and to induce a cell cycle arrest in a concentration-dependent manner in HeLa cells, as evidenced by flow cytometry. A noncancerous human fibroblast cell line (MRC-5) was used to test the selectivity of kokusaginine and skimmianine. Fluorescent microscopy after Hoechst 33258 + propidium iodide double staining revealed concentration-dependent nuclear condensation and disturbed cell membrane integrity. The apoptotic potentials of kokusaginine and skimmianine were proved by assaying caspase-3. The presented results demonstrate that kokusaginine and skimmianine can be recommended as appropriate starting structures for the design and synthesis of further quinoline analogs with improved efficacy.
Keywords: Quinoline alkaloids